Pengaruh Kepemilikan Institusional Dan Ukuran Perusahaan Terhadap Kebijakan Hutang Dan Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bei) - Elva Nuraina (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2012)
AbstractThis study aims to test empirically: 1)the influence of institutional ownership on corporate value, 2)the effect of firm size on firm value, 3)the influence of institutional ownership on debt policy, 4)the effect of firm size on debt policy. The population in this study is a public company in Indonesia Stock Exchange with manufacturing companies in the sample. Sampling method using purposive sampling. Analytical techniques used in this study using multiple linear regression which include normality test, test classic assumptions and hypothesis testing. The results showed that 1) the institutional ownership has a significant effect confirm value, 2) the size of the company has a significant effect on firm value, 3) institutional ownership have a significant effect on corporate debt policy, 4) firm size had no significant effect on corporate debt policy.